Machines, Computations, and Universality 7th International Conference, MCU 2015, Famagusta, North Cyprus, September 9-11, 2015, Proceedings - Durand-Lose, Jerome; Nagy, Benedek (Theoretical Computer Science and General Issues,, 2015)
This book constitutes the refereed proceedings of the 7th International Conference on Machines, Computations, and Universality, MCU 2015, held in Famagusta, North Cyprus, in September 2015. The 10 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 23 submissions. MCU explores computation in the setting of various discrete models (Turing machines, register machines, cellular automata, tile assembly systems, rewriting systems, molecular computing models, neural models, etc.) and analog and hybrid models (BSS machines, infinite time cellular automata, real machines, quantum computing, etc.).